2003
DOI: 10.1002/jnr.10560
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of sciatic nerves of adult rats induced by extracts from distal stumps of pre‐degenerated peripheral nerves

Abstract: Despite numerous experimental and clinical attempts to reconstruct injuries of peripheral nerves, the methods developed until now have not been sufficiently effective. We examined the influence of extracts (postmicrosomal fractions) obtained from non-pre-degenerated or 7-day-pre-degenerated distal segments of peripheral nerves on the regeneration of injured sciatic nerves of male adult rats. The extracts were introduced to the site of injury with autologous connective tissue chambers filled with fibrin. Refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
1
8
0
2
Order By: Relevance
“…Our previous studies revealed that the extracts obtained from degenerating nerves strongly enhance the morphological features of nerve regeneration in so-called dead-ended autologous connective-tissue chambers. 25 The current results seem to be greatly important from the practical point of view because they are very similar to the results observed by us as well as by many other researches in standard nerve autograft techniques. 4,35,38,40 We also demonstrated, in all groups, that the greatest numbers of AChE-positive nerve fibers were present in the proximal part of the chambers, where bulges could be observed.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our previous studies revealed that the extracts obtained from degenerating nerves strongly enhance the morphological features of nerve regeneration in so-called dead-ended autologous connective-tissue chambers. 25 The current results seem to be greatly important from the practical point of view because they are very similar to the results observed by us as well as by many other researches in standard nerve autograft techniques. 4,35,38,40 We also demonstrated, in all groups, that the greatest numbers of AChE-positive nerve fibers were present in the proximal part of the chambers, where bulges could be observed.…”
Section: Discussionsupporting
confidence: 91%
“…9,11,41 An additional supply of the chambers with known neuroactive substances, BDNF and PD fractions, resulted in further regenerative improvement. 25 We chose BDNF for the reference group because it was shown that collagen tubulization and BDNF enhance functional recovery of peripheral nerves, and its beneficial effect on motoneurons is well- documented. 13À15,31,42À47 In postmicrosomal fractions, obtained on day 7 of degeneration, a majority of neurotrophic activity is attributed to increased levels of nerve growth factor (NGF) and not BDNF, because the level of the latter is low on that day and reaches its maximum on day 28 of nerve degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cytokines and growth factors play important roles during the development and regeneration of peripheral nerves (Chen et al 2000;Chen et al 2001a, b;Lee et al 2003;Marcol et al 2003). Among the factors, neurotrophic factors and extracellular matrix proteins are regarded as growth-promoting factors that stimulate neurite outgrowth of neurons and promote proliferation and migration of SCs (Anton et al 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Many investigators equate autotomy behavior with the presence of neuropathic pain in animals (Wall et al, 1979; Coderre et al, 1986; Marcol et al, 2003). The mechanisms of autotomy are not clearly understood, but it is acknowledged that both central and peripheral mechanisms are involved.…”
Section: Discussionmentioning
confidence: 99%